A Local Authority v JB [2020] EWCA Civ 735 and A Local Authority v AW [2020] EWCOP 24: Rethinking Sexual Capacity?. (17th September 2020) - Pritchard-Jones, Laura
Abstract: In A Local Authority v JB and A Local Authority v AW, the Court of Appeal and Court of Protection, respectively, had to consider questions regarding decision-making about sexual relationships. This case commentary suggests that both decisions are to be welcomed in many ways, not least in the primacy they give to the role of consent within sexual relationships. However, working through their implications also reveals a number of perplexing legal and practical binds that cannot easily be overcome, and that in fact stem from the way that the Mental Capacity Act 2005 itself works. In light of this, the commentary concludes by suggesting that it is likely that there will be continued dissatisfaction with this area of law and hints that the time may have come to rethink sexual capacity.